Expresión (xy+(y¬z∨xz))z∨¬x¬y¬z
El profesor se sorprenderá mucho al ver tu solución correcta😉
Solución
Solución detallada
(x∧y)∨(x∧z)∨(y∧¬z)=(x∧z)∨(y∧¬z)z∧((x∧y)∨(x∧z)∨(y∧¬z))=x∧z(z∧((x∧y)∨(x∧z)∨(y∧¬z)))∨(¬x∧¬y∧¬z)=(x∨¬z)∧(z∨¬x)∧(z∨¬y)
(x∨¬z)∧(z∨¬x)∧(z∨¬y)
(x∨(¬z))∧(z∨(¬x))∧(z∨(¬y))
Tabla de verdad
+---+---+---+--------+
| x | y | z | result |
+===+===+===+========+
| 0 | 0 | 0 | 1 |
+---+---+---+--------+
| 0 | 0 | 1 | 0 |
+---+---+---+--------+
| 0 | 1 | 0 | 0 |
+---+---+---+--------+
| 0 | 1 | 1 | 0 |
+---+---+---+--------+
| 1 | 0 | 0 | 0 |
+---+---+---+--------+
| 1 | 0 | 1 | 1 |
+---+---+---+--------+
| 1 | 1 | 0 | 0 |
+---+---+---+--------+
| 1 | 1 | 1 | 1 |
+---+---+---+--------+
(x∧z)∨(¬x∧¬y∧¬z)
(x∧z)∨(z∧¬z)∨(x∧z∧¬x)∨(x∧z∧¬y)∨(x∧¬x∧¬y)∨(z∧¬x∧¬z)∨(z∧¬y∧¬z)∨(¬x∧¬y∧¬z)
(x∧z)∨(z∧(¬z))∨(x∧z∧(¬x))∨(x∧z∧(¬y))∨(x∧(¬x)∧(¬y))∨(z∧(¬x)∧(¬z))∨(z∧(¬y)∧(¬z))∨((¬x)∧(¬y)∧(¬z))
Ya está reducido a FNC
(x∨¬z)∧(z∨¬x)∧(z∨¬y)
(x∨(¬z))∧(z∨(¬x))∧(z∨(¬y))
(x∨¬y)∧(x∨¬z)∧(z∨¬x)
(x∨(¬y))∧(x∨(¬z))∧(z∨(¬x))